Evaluation of CPAP mask performance during 3 years of mask usage: time for reconsideration of renewal policies? - Adel Bachour; Atte Laaka; Maria Hollmén (BMJ Open Respiratory Research)
Background Continuous positive airway pressure (CPAP) mask renewal policies vary inside and between countries. There are no independent studies on the optimal mask renewal frequency. We aimed to evaluate CPAP mask function over time in a real-life clinical setting, and to compare the results against current renewal policies.Methods Daily performance data of 1846 CPAP masks (65% nasal, 22% nasal pillows, 12% oronasal) were recorded from 450 participants (68% male, mean age 59 years) with obstructive sleep apnoea. The unintentional leak, Apnoea-Hypopnoea Index (CPAP-AHI) and usage data were exported from the CPAP device.Results Of 656 324 nights of CPAP usage, the mean renewal time was 497 days (SD 327), mean leak 5.7 L/min (SD 8.1) and CPAP-AHI 3.8 events/h (SD 3.6). The difference in mean leak between one (5.2 L/min, SD 7.5), 12 (6.0 L/min, SD 10.2) and 24 months (5.8 L/min, SD 7.5) was minimal (p=0.59). Mean CPAP-AHI remained normal and unchanged in nasal masks and pillows up to 30 months, and was highest in oronasal masks. Different mask manufacturers performed similarly. Masks’ daily or total usage did not affect the results. Shifting the mask renewal policy to 24 months could reduce the mask-related cost up to 50%–88%.Conclusions Nasal masks and pillows could be used at least 2 years without significant changes in unintentional leak and CPAP-AHI. We suggest updating the mask renewal policies of nasal masks and pillows; results on oronasal masks and other manufacturers CPAP devices need further verification.